The large-scale structure of uniformly sheared turbulence and its distortion by a solid wall at rest or in motion. - Kislich-Lemyre, Benoit C. (University of Ottawa (Canada), 2002)
The large-scale structure of sheared turbulence has been documented with the use of flow visualization and laser-Doppler velocimetry. The study includes nominally unbounded uniformly sheared flow (USF), turbulent boundary layers, used as reference, and the effects of stationary and moving walls on USF. USF with statistical properties comparable to those in earlier wind-tunnel studies was successfully generated in a water tunnel. Horseshoe-type structures, generally considered as one of many typical eddies in turbulent boundary layers and also observed in jets, wakes and mixing layers, have been observed in USF, for the first time experimentally. This indicates that the presence of a wall is not required for such structures to develop. These structures evolved by being stretched and rotated by the velocity gradient. The dominant large-scale structures in USF were observed to be similar to those found in the outer layer of a turbulent boundary layer, albeit much less organized. No evidence of streaks was found in the core USF, while streaks were clearly visible near the wall in the reference turbulent boundary layer study. The energetic bursting of horseshoe structures that has been observed in boundary layers was not observed in USF, however the heads of the horseshoe structures were often noticed to travel in the transverse direction. The study of USF in the vicinity of a wall moving at the local mean speed has been the first of its kind, as previous studies with a moving wall were conducted in uniform flow. The present research has demonstrated that shear associated with friction with the wall (no-slip condition) is the major factor in the production of turbulence, and that the physical barrier (no-penetration condition) of the wall acts as a suppressant to oncoming turbulence structures and provides organization to their development. The moving wall studies were extended to cases with the wall moving faster than the local mean velocity and the wall moving in a direction opposite to that of the local mean velocity. These studies provided interesting information on the interaction of turbulence with the mean shear and the effects of the wall.
Keywords: Engineering, Mechanical.